Myxedema Coma Complicated by Pancytopenia - Charles T. Mupamombe; Felix M. Reyes; Derek B. Laskar; Joseph Gorga (Case Reports in Medicine)
Hypothyroidism is common, with an extreme manifestation of myxedema coma if untreated. Hematologic consequences of myxedema coma include mild leukopenia and anemia, rarely pancytopenia. We present a patient with typical symptoms of myxedema coma, but found to be pancytopenic, with sustained response to levothyroxine and blood transfusion for anemia.